Ownership, bank size, capitalization and bank performance: Evidence from India - Neeraj Gupta; Jitendra Mahakud (Cogent Economics & Finance, 2020)
This study focuses on assessing the role of various bank-specific, industry-specific and macroeconomic determinants in Indian commercial banks performance. Performance of the Indian banks has been measured by Return on Assets (ROA), Return on Equity (ROE) and Net Interest Margin (NIM) and Pre-provision profit ratio. The study analyses impact of various bank-specific factors like bank size, capital ratio, risk, cost to income ratio, funding cost, revenue diversification, labour productivity and bank age on bank performance. It also tries to assess the relationship between various bank-specific and industry-specific variables like bank concentration, inflation rate and GDP growth rate with bank performance. Fixed effects estimation model and Generalized Method of Moments (GMM) have been used on a panel data of 19 years for 64 commercial banks of India. The findings reveal that private sector banks are more profitable than the public sector banks. Additionally, the results of the study show that bank size, non-performing loan ratio and revenue diversification are the major determinants of the commercial banks performance in India. Furthermore, the results reveal that during the crisis period the impact of bank size, bank age, labour productivity and revenue diversification on the performance of the Indian banks is robust. The higher non-government stake leads to the enhanced performance of the commercial banks in India. The higher capital adequacy leads to the increase in the performance of the banks. The larger banks are less profitable. The results provide better insights about the determinants of Indian banks profitability.
Keywords: 330; bank size; bank-specific; fixed effect; GMM; macroeconomic; NIM; private sector banks; public sector banks